Pig farming systems and cysticercosis in northern Uganda - Kungu, Joseph M.; Masembe, C.; Apamaku, M.; Akol, Joyce; Amia, Winfred C.; Dione, Michel M. (Centre de coopération internationale en recherche agronomique pour le développement, 2019)
Rudimentary non-market-oriented pig rearing systems have been implicated in the persistence of Taenia solium cysticercosis, an endemic disease of high public health concern in Uganda. We investigated the seroprevalence and key predisposing factors of the disease in Moyo and Lira, two pig-producing districts in Northern Uganda. Cross-sectional serosurveys were conducted in 428 pig farms (Moyo, 262; Lira, 166). Farmers kept on average two adult pigs per herd. Tethering was a common practice in rural areas; free-ranging less so. Confinement of pigs in pens was characteristic of periurban farming systems. Pigs were mainly fed crop residues and forages in the rainy season, and swill and crop residues in the dry season. The majority of farmers of the survey were women (55%) above 45 years old, and 51% of farmers had attained primary school education. A total of 723 pig serum samples were collected, 403 in Moyo, and 320 in Lira. They were analyzed for Taenia spp. antigens using B158C11A10/B60H8A4 Antigen-ELISA. The overall animal seroprevalence of Taenia spp. serum antigen was 10.4% (95% confidence interval [CI]: 4.9–17.6), with 13.2% (95% CI: 7.1– 21.2) the highest in Moyo vs 6.9% (95% CI: 2.9–13.9) in Lira. The herd-level seroprevalence was estimated at 13.7% (95% CI: 9.8–18.5) in Moyo and 11.4% (95% CI: 7.0–17.2) in Lira. Out of 12 explanatory variables assessed for association with the observed seroprevalence, only the district of origin was significant (p = 0.01). Pigs originating from Lira were a protective factor against Taenia spp. cysticercosis (odds ratio: 0.54). These findings highlight the urgent need for an awareness campaign with prevention and control measures to minimize the risk of transmission to pork consumers in these districts.